Different Prognosis among Pregnant Patients with COVID-19 Infection - Leila Mousavi-Seresht; Maryam Dehghan; Tahereh Khalili-Borujeni (مجله دانشکده پزشکی اصفهان, 2020)
Background: Infected pregnant women with new coronavirus (COVID-19) has raised concerns about the increased risk of complications due to pregnancy, the presence of predisposing factors, multiple possible diagnoses, and treatment limitations.